Hemoglobin, alkalic phosphatase, and C‐reactive protein predict the outcome in patients with liposarcoma. Issue 5 (13th March 2015) - Panotopoulos, Joannis; Posch, Florian; Alici, Benjamin; Funovics, Philipp; Stihsen, Christoph; Amann, Gabriele; Brodowicz, Thomas; Windhager, Reinhard; Ay, Cihan
ABSTRACT: Data on prognostic biomarkers in soft tissue sarcomas are scarce. The aim of the study was to define prognostic markers in patients with a liposarcoma, a subtype of sarcoma derived from adipose tissue. We restrospectively reviewed 85 patients with liposarcoma treated at our department from May 1994 to October 2011. Kaplan–Meier curves, uni‐, and multivariable Cox proportional hazard models and competing risk analysis were performed to evaluate the association between putative biomarkers with disease‐specific and overall survival. We observed a significant association between both alkalic phosphatase (ALP; subhazard ratio [SHR] per 1 unit increase: 1.35; 95%CI 1.10–1.65; p  = 0.005) and C‐reactive protein (CRP; SHR per 1 mg/dl increase: 2, 57; 95%CI 1.36–4, 86; p  = 0.004) with disease‐specific survival. Hemoglobin (Hb) (HR per 1 g/dl increase: 065; 95%CI 0.48–0.87; p  = 0.003) was associated with overall survival. These associations prevailed after multivariable adjustment for AJCC tumor stage. This study identifies CRP and ALP as novel independent predictors of disease‐specific survival in patients with liposarcoma. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:765–770, 2015.